2004
DOI: 10.1080/07315724.2004.10719361
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid-Rich Dark Chocolate Improves Endothelial Function and Increases Plasma Epicatechin Concentrations in Healthy Adults

Abstract: Flavonoid-rich dark chocolate improves endothelial function and is associated with an increase in plasma epicatechin concentrations in healthy adults. No changes in oxidative stress measures, lipid profiles, blood pressure, body weight or BMI were seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
288
5
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(315 citation statements)
references
References 44 publications
10
288
5
12
Order By: Relevance
“…We did not observe any differences in CBF at the time of ischemia and reperfusion, but this absence of effect might be because only a single dose of EC was used. In a small clinical study, participants who received 46 mg of EC daily for over a period of 2 weeks showed endothelium-dependant vasodilation (Engler et al, 2004). It is possible that chronic treatment rather than a single dose is required to observe differences in CBF.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any differences in CBF at the time of ischemia and reperfusion, but this absence of effect might be because only a single dose of EC was used. In a small clinical study, participants who received 46 mg of EC daily for over a period of 2 weeks showed endothelium-dependant vasodilation (Engler et al, 2004). It is possible that chronic treatment rather than a single dose is required to observe differences in CBF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that dark chocolate consumption reduces blood pressure (Grassi et al, 2005b;Grassi et al, 2008), improves insulin sensitivity as shown by significantly higher QUICKI (quantitative insulin sensitivity check index) measurements (Grassi et al, 2008), improves vascular endothelial function and reverses vascular dysfunction (Engler et al, 2004;Grassi et al, 2005b;Wang-Polagruto et al, 2006), reduces insulin resistance as evidenced by significantly lower HOMA-IR (homeostasis model assessment of insulin resistance) (Grassi et al, 2005a) measurements, and increases serum total antioxidant capacity (Wan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…(http://www.nal.usda.gov/fnic/ foodcomp/search/), the latter two being saturated fats. Cocoa products are also very rich in plant phytochemicals, especially flavonoids, which are now objects of increased scientific attention due to their potential health benefits (Engler et al, 2004;Grassi et al, 2005a;Wang-Polagruto et al, 2006;Almoosawi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they documented a decrease in BP (SBP: −4.8 ± 1.03 mmHg, p < 0.0001; DBP: −3.03 ± 1.07 mmHg, p = 0.0011), and an improvement in endothelial function (23). However, in four different studies, flavanol-rich cocoa (234, 259, 550, 805 mg flavanols per day, respectively) did not improve BP levels compared to placebo in normotensive subjects (45)(46)(47)(48).…”
Section: Epidemiological Evidencementioning
confidence: 96%
“…Flavanol-rich chocolate (213 mg procyanidins, 46 mg epicatechin) consumption significantly improved FMD in 21 healthy subjects also over a 2-week period (p = 0.024). Moreover, plasma epicatechin concentrations markedly increased after 2 weeks in the active treatment group, suggesting that the effect on vascular function was flavanolmediated (46). In the Flaviola Health Study, a 1-month CF intake increased FMD over control by 1.2% (95% CI, 1.0-1.4) and decreased pulse wave velocity by 0.4 m/s (95% CI, 0.8-0.04 m/s) (27).…”
Section: Cocoa and Vascular Function: Interventional Studiesmentioning
confidence: 98%